Controlling condensation and frost growth with chemical micropatterns - Boreyko, J. B.; Hansen, Ryan R.; Murphy, K. R.; Nath, S.; Retterer, S. T.; Collier, C. P. (My University, 2016)
In-plane frost growth on chilled hydrophobic surfaces is an inter-droplet phenomenon, where frozen droplets harvest water from neighboring supercooled liquid droplets to grow ice bridges that propagate across the surface in a chain reaction. To date, no surface has been able to passively prevent the in-plane growth of ice bridges across the population of supercooled condensate. Here, we demonstrate that when the separation between adjacent nucleation sites for supercooled condensate is properly controlled with chemical micropatterns prior to freezing, inter-droplet ice bridging can be slowed and even halted entirely. Since the edge-to-edge separation between adjacent supercooled droplets decreases with growth time, deliberately triggering an early freezing event to minimize the size of nascent condensation was also necessary. These findings reveal that inter-droplet frost growth can be passively suppressed by designing surfaces to spatially control nucleation sites and by temporally controlling the onset of freezing events.
Citation: Boreyko, J. B., Hansen, R. R., Murphy, K. R., Nath, S., Retterer, S. T., & Collier, C. P. (2016). Controlling condensation and frost growth with chemical micropatterns. Scientific Reports, 6, 15. doi:10.1038/srep19131
Keywords: Superhydrophobic Surfaces; Dropwise Condensation; Heat-Transfer; Supercooled Water; Ice Nucleation; Solid-Surfaces